2019
DOI: 10.2147/ott.s228798
|View full text |Cite
|
Sign up to set email alerts
|

<p>LncRNA LINC00461 Promotes Colorectal Cancer Progression via miRNA-323b-3p/NFIB Axis</p>

Abstract: BackgroundLncRNA LINC00461 has been reported to play crucial regulatory roles in a variety of biological processes, including cell migration, cell invasion and cancer progression. However, its biological role in colorectal cancer (CRC) is completely unknown. The aim of our study was to explore the function of LINC00461 on CRC cells and the underlying mechanism.Materials and methodsCRC tumor tissues and cell lines derived from hospital and corporation. The expression level of LINC00461 in CRC tissues and cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Mounting evidence has confirmed that miRNAs could target certain mRNAs and further regulate the development of serious diseases [31][32][33]. To further clarify the effect of miR-486-3p on lung cancer cells, bioinformatics and luciferase reporter assays were applied.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence has confirmed that miRNAs could target certain mRNAs and further regulate the development of serious diseases [31][32][33]. To further clarify the effect of miR-486-3p on lung cancer cells, bioinformatics and luciferase reporter assays were applied.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several studies have reported the tumor-related function of LINC00461 in various tumors. For instance, LINC00461 was shown to strengthen the colorectal cancer cells' proliferation and invasion ability by miRNA-323b-3p/NFIB Axis [ 25 ]. LINC00461 was reported to be highly expressed in lung tumor, and its knockdown suppressed the tumor cells' proliferation and metastasis via miR-4478/E2F1 [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, upstream mediators are able to affect the STAT3/EMT axis. Nuclear factor I/B (NFIB) participates in normal somatic development and recent studies have revealed its role in cancer progression and development [256,257]. NFIB is able to induce Akt phosphorylation.…”
Section: Other Molecular Signaling Pathways Regulate Stat3mentioning
confidence: 99%